(untitled) (University of Khartoum Engineering Journal, 2022)
Intrinsic swelling was evaluated for seventeen potentially expansive clay samples obtained fromdifferent parts of Sudan. A swell percent test, where the test samples were statically compacted at air drytemperature to the same dry density (1.35 g/cm3) and allowed to swell was used as a measure for intrinsicswelling. Physico-chemical properties were measured for all the samples to assess the effect of these properties onintrinsic swelling. The physical properties included, gradation (clay, silt and sand contents), Atterberg limits (LL,PL and SL), linear shrinkage and free swell whereas the chemical properties included cation exchange capacityCEC, exchangeable sodium percent ESP and sodium absorption ratio SAR. The investigation has shown thatintrinsic expansiveness is well related to linear shrinkage and that linear shrinkage alone is a good candidate forassessing both the swelling and shrinkage potential of clay soils. However, clay activity is found to be a poorindicator of intrinsic expansiveness if the well known evaluation standards are adopted. Intrinsic expansiveness iswell related to LL, PI and SI and these parameters could be used for its assessment. The CEC showed poorrelationship whereas ESP and SAR showed no relationship with intrinsic expansiveness